2006
DOI: 10.1345/aph.1h424
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacy and Medication Safety

Abstract: W hile medication safety and preventive adverse drug event strategies have been more prominently reported in the medical literature over the last decade, the pharmacist's role in improving the safety of medication use has been a part of the pharmacy literature since the 1960s. The inaugural issue of The Annals of Pharmacotherapy was published in January 1967 as Drug Intelligence, and over the years the journal has undergone a few more name changes. The Annals of Pharmacotherapy was started by a dedicated group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…By the mid-1960s, pharmacists transitioned towards a more patient-centered approach, introducing the concept of clinical pharmacy [1,2,4], the beginning of an evolution detailed further in Figure 1. Pharmacists actively participated in optimizing patient medication therapies within hospital settings [13]. While pharmacists have been examining medicine charts and offering recommendations to prescribers since the 1980s, this practice was not yet widely adopted in primary care settings during that period [4,14].…”
Section: History Of Medication Reviewmentioning
confidence: 99%
“…By the mid-1960s, pharmacists transitioned towards a more patient-centered approach, introducing the concept of clinical pharmacy [1,2,4], the beginning of an evolution detailed further in Figure 1. Pharmacists actively participated in optimizing patient medication therapies within hospital settings [13]. While pharmacists have been examining medicine charts and offering recommendations to prescribers since the 1980s, this practice was not yet widely adopted in primary care settings during that period [4,14].…”
Section: History Of Medication Reviewmentioning
confidence: 99%
“…[2,6] Pharmacists play various roles in the healthcare system and Understanding Pharmacist Communication and Medication Errors: A Systematic Literature Review pharmaceutical care requires the pharmacist's involvement to prevent and solve drug related problems. [7] Additionally, pharmacists help with improving safety of medication use, [8] quality assurance and care services, which can reduce or eliminate the risk of errors. [9] Medication errors can be due to prescribing, dispensing and drug administration errors and related factors to the drug distribution chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Significant among these interventions is the role of pharmacists in maximizing the safe, effective, and efficient use of medicines [16][17][18][19][20]. Bond and Raehl [21] showed that pharmacy practice has the propensity to improve patient outcomes, reduce rates of adverse events and mortality, and maintain value over time.…”
Section: Introductionmentioning
confidence: 99%